Heroism in Chairil Anwar’s Poems - Rachmi Laya (Transbahasa, 2022)
The present study aimed (1) to find out clearly heroistic meaning in Chairil Anwar’s poem, and what the purpose of expressing it, (2) to see how Chairil Anwar chose diction in his poem and how did combined the words, and (3) to find out what kinds of heroistic meaning. This research employed a structural approach. Structural approach moves from concept intrinsic aspect structurally as totality works which formed by aspects correlated each other. This research is a library research. Thus the data collected involves the process of reading, understanding, and giving meaning by interpreting the data. From 73 poems, this research took 17 poems as the samples. The data were collected by reference study, and analyzed by identifying the words or lines contained heroism, classifying, categorizing, and interpreting the data based on heroism aspects. The study found that Analysis of the meaning of poem Chairil Anwar’s poem had a deep heroistic meaning. As a matter fact, it could be seen by using diction and his combining words. The diction was used could rise imagination. Imagining and concreting words had compact correlation, it used style. There after imagining and using style would rise certain sound. The sounds could rise heroistic sound. In other words, factually the heroism in Chairil Anwar’s poem be formed by diction, combining words and sounds.